Application of the PjBL Model to Chemical Materials to Improve Students' Creative Thinking Skills and Entrepreneurial Interests - Masykuratu Amalia; M. Adlim; Ibnu Khaldun; Sri Winarni; M. Hasan (Jurnal Penelitian Pendidikan IPA, 2024)
Project Based Learning (PjBL) has many advantages but has not been widely implemented, let alone linked to entrepreneurial activities in schools. Entrepreneurship in schools, especially those taught by chemistry teachers, still has not produced crafts that link chemical knowledge therein. The aim of the research carried out was to analyze how much influence the application of the PjBL model has in improving students' creative thinking skills and entrepreneurial interest. The research method uses a one group pretest-posttest design approach. The research sample was selected using proportional sampling with data collection techniques, namely test techniques and distributing questionnaires which were then analyzed using the paired sample t test. Based on the results of the research that has been carried out, it can be concluded that there is a positive significant difference between before and after treatment. This shows an increase in students' creative thinking abilities and entrepreneurial interest after implementing the PjBL learning model.